The Influence of Electronic Word of Mouth (E-WOM) and Travel Motivation toward the Interest in Visiting Lombok, Gender as a Mediator - Zakky Fahma Auliya; Imanda Firmantyas Putri Pertiwi (State Institute of Islamic Studies (IAIN) Salatiga, 2019)
The background of this research is the decreased number of tourists, either domestic or foreign tourists, visiting Lombok, in which Lombok is a halal tourism destination in Indonesia. This research aims to analyze the influence of electronic word of mouth (e-WOM) and travel motivation toward the interest in visiting Lombok with gender as the mediator, using a purpose-sampling technique on its sample collection. The respondents of this research are university students in Surakarta. The number of questionnaires spread by the researcher is 316 samples and the samples that can be used are 264. This research uses the analysis tool of SPSS 22 with a scale of 1-5. The result shows that e-WOM and travel motivation influence the interest in visiting Lombok, while the influence with gender as the mediator shows that males have a bigger influence toward the use of e-WOM and travel motivation toward the interest of visiting Lombok